Detección de hipertensión ocular con tonómetro de Goldmann frente al Neumotonómetro en pacientes adultos de consulta externa, en el Instituto Regional de Oftalmología JSU- Trujillo - Palma Pinedo, Práxedes Jesús (2019)
OBJECTIVE: To detect ocular hypertension with the Goldmann tonometer against the pneumotometer in adult outpatients, at the Regional Institute of Ophthalmology-JSU -Trujillo 2019. MATERIAL AND METHODS: In a sample of 200 eyes of 100 patients, who go to an external ophthalmology office, who meet the inclusion criteria; The nursing staff takes the intraocular pressure with the pneumotometer (NIDEK NT-510) in both eyes. This information is written on the data collection sheet; Subsequently, the intraocular pressure is taken with the Goldmann tonometer performed by an assistant ophthalmologist, whose data is written on the data collection sheet. The central corneal thickness of the patient is also calculated with the corneal pachymeter. RESULTS: IOP> 21, of the right eye, is obtained in 67 patients with T. Goldmann as well as with the pneumotometer. In the left eye, with IOP> 21, it is detected with NT in 79 patients, compared with 76 patients taken with TG. Of the total patients in the study, 36% were male and 64% were female. In the distribution by the age range, it was obtained that the highest percentage was constituted by the range between 60 to 69 years, with 36%, then the range between 70 to 79 years with 33% and finally 21 % of patients were in the range between 50 to 59 years. In our study we also detected 26 right eyes and 26 left eyes of patients with thickness corneal central in the range considered normal in our study. Sensitivity in the pneumotometer was 100%, The specificity in the pneumotometer was 100%. The Positive Predictive Value was 33% and the Negative Predictive Value was 79%. CONCLUSIONS: In our study the detection of ocular hypertension with Pneumotometer is as effective as the Goldmann tonometer (applanation tonometry), in adult outpatients, at the Regional Institute of Ophthalmology-JSU, Trujillo, 2019.